GENDER BASED VIOLENCE IN KWARA STATE, NIGERIA: A QUALITATIVE ANALYSIS - Olushola Idris-Iyekolo; Omoshalewa Lasbat Akinsemoyin (Sociology Education, Teaching Training and Education Faculty, Muhammadiyah University of Kupang, 2025)
This study investigates the causes, consequences, and preventive measures of gender-based violence (GBV) in Kwara State, guided by three research objectives addressed through a qualitative approach. The participants consisted of ten university lecturers from diverse fields in Ilorin, Kwara State, who were purposively selected. Semi-structured interviews were conducted, and the data were analyzed using thematic analysis. The study found that the causes of GBV are complex and deeply rooted in cultural, social, economic, and political factors. The consequences affect individuals, families, and the broader community on multiple levels. To combat this pervasive issue, the study proposes a comprehensive set of localized preventive measures. These include community engagement, strengthening legal frameworks, economically empowering women, creating support systems, integrating GBV responses into healthcare services, educational initiatives, cultural reform, and ensuring adequate resource allocation by local governments.